(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The main goal of the study is to shed light on what modern wars are, from an anthropological point of view, by observing and documenting the origins of the classification of these wars, the changes that have been identified with them, and the key features that differentiate them, in the light of contemporary models and realities. By applying the historical and descriptive analytical method. Research has concluded that the concepts coined so far for modern wars-or new wars-are mostly meant as fourth-generation wars and that what is called "fifth-generation wars" is nothing but an extension of this generation or another type of modern anthropology-based warfare. And that the foreign strategies behind modern wars relied on the study of the circumstances of communities and cultures with various sociological and anthropological dimensions. Across modern wars, they have served to fracture and disintegrate their unity by reviving political , ideological, cultural , linguistic, and social divisions and turning them into internal conflicts and conflicts at the cost of the national state. As a result, the first way to limit the occurrence of these wars is to build collective consciousness and direct national knowledge to combat them.